Alfalfa Intervention Alters Rumen Microbial Community Development in Hu Lambs During Early Life - Yang, Bin; Le, Jiaqing; Wu, Peng; Liu, Jianxin; Guan, Le L.; Wang, Jiakun (Frontiers in Microbiology, 2018)
The pre-weaning period is crucial for rumen developmental plasticity, which can have a long-term impact on animal performance. Understanding the rumen microbiota during early life is important to elucidate its potential role in rumen development. In this study, the rumen microbiota of 10-day-old Hu lambs fed either milk replacer (B-10), milk replacer and starter (STA) or milk replacer and starter supplemented with alfalfa (S-ALF) in the pre- (d17, 24, and 38) and post-weaning periods (d45 and 66) were assessed to characterize rumen microbial colonization during early life and its response to fiber intervention. In the rumens of B-10 lambs, 498 operational taxonomic units belonging to 33 predominant genera were observed, and the top six predicted functions included “Membrane transport,” “carbohydrate metabolism,” “amino acid metabolism,” “replication and repair,” “translation,” and “energy metabolism.” Prevotella, Succinivibrio, Bifidobacterium, and Butyrivibrio abundances were increased at d38 for both STA and S-ALF groups compared to the B-10 group, whereas fibrolytic bacteria of the taxa Lachnospiraceae and Treponema were only increased in the S-ALF group at d38. A number of saccharolytic bacteria (Bacteroidaceae), organic acid-producing bacteria (Coprococcus and Actinomyces), proteolytic and amino acid fermenters (Fusobacterium) and fibrolytic bacteria (unclassified Ruminococcaceae) were significantly decreased in the STA lambs but not in the S-ALF lambs at d38. After weaning and exposed to alfalfa, the rumen microbial composition in the STA group started to appear similar to that of the S-ALF lambs. The relative abundance of unclassified Clostridiales was higher in S-ALF lambs than STA lambs after weaning. Spearman’s correlation analysis showed positive relationships between unclassified Lachnospiraceae, unclassified Clostridiales, Treponema, unclassified Bacteroidales, Coprococcus and crude protein intake, neutral detergent fiber intake, and plasma β-hydroxybutyrate. The unclassified Lachnospiraceae and Treponema were also positively correlated with average daily gain. Our results revealed that alfalfa stimulated changes in rumen microbiota during the pre- and post-weaning periods and was consistent with rumen development for better feed intake and animal performance before and after weaning. The findings of this study provide clues for strategies to improve rumen function through manipulation of the rumen microbiota during early life.